Una rubrica di cultura (e) politica. Lo Stato negli argomenti di cultura di Gramsci - Di Blasio, Federico (Las Torres de Lucca. International Journal of Political Philosophy, 2026)
This essay examines Antonio Gramsci’s prison writings through the lens of the rubric Argomenti di cultura and its connection to his evolving conception of the State. Starting from the philological and historical context of the Quaderni del carcere, the study highlights how Gramsci’s organizational method—his “cultural rubrics”—served as both a tool for intellectual orientation and a strategy for political reflection. Focusing on the notes grouped under Argomenti di cultura and Nozioni enciclopediche, the paper argues that these writings reveal Gramsci’s effort to broaden the semantic and conceptual scope of the State as an “integral” unity of political and civil society. By linking culture and politics dialectically, Gramsci conceives the State not as a mere apparatus of coercion, but as an educative and ethical force aimed at shaping a new type of citizen. Ultimately, political transformation, for Gramsci, is inseparable from the creation of a new culture.
Keywords: Gramsci; Culture; Politics; Society; State